KEBERTERIMAAN GURU SEKOLAH DASAR TERHADAP MEDIA PEMBELAJARAN BERBASIS WEB PADA MATERI PERKEMBANGAN TEKNOLOGI KELAS 3 SEKOLAH DASAR - Christin Dwi Putri Septian (STKIP Subang, 2023)
This study aims to determine whether elementary school teachers are amenable to incorporating online learning materials into the class 3 technology development curriculum. In web-based learning resources, information and communication technology is utilized to support teaching and learning. This study will identify the factors that affect teachers' acceptability of using online learning resources. Additionally, the advantages of media use for educators and students will be examined. The use of online learning resources in elementary schools for class III is anticipated to present challenges and opportunities, which this study will help to clarify.